Legal Culture in Law Enforcement Related to Child Criminal Offenses - Anwar*, Aulia Citra; Ratnawati, Elfrida (Riwayat: Educational Journal of History and Humanities, 2023)
The existence of negotiations in criminal acts involving children aged 12-18 years, as well as the legal vacuum in criminal acts involving children under 12 years old, indicates that law enforcement for juvenile offenses has not been optimal. Society seems resigned to the legal system, leaving them no choice but to follow the existing Legal Culture. By using a normative juridical approach and a descriptive-analytical method, this research will provide an overview of legal culture in the enforcement of laws related to juvenile crimes. The results of this study indicate that the Legal Culture is still very low, prompting a recommendation for legal reforms such as creating regulations regarding repeated offenses in crimes involving children under 12 years old, establishing a Child Police and a Children's Court, and using social research through the Children's Court as a stepping stone to improve the Legal Culture.